Step * 2 1 of Lemma rv-compass-compass-lemma

.....assertion..... 
1. : ℝ^2
2. : ℝ^2
3. : ℝ^2
4. : ℝ^2
5. a ≠ c
6. ↓∃p,q:ℝ^2. (((d(a;b) d(a;p)) ∧ (d(c;d) d(c;q))) ∧ (d(c;p) ≤ d(c;d)) ∧ (d(a;q) ≤ d(a;b)))
7. ∃u,v:ℝ^2
    (((||u|| d(a;b)) ∧ (||u a|| d(c;d)))
    ∧ ((||v|| d(a;b)) ∧ (||v a|| d(c;d)))
    ∧ (((d(a;b)^2 d(c;d)^2) ||c a||^2^2 < (r(4) ||c a||^2 d(a;b)^2))
       (r2-left(u;c a;λi.r0) ∧ r2-left(v;λi.r0;c a))))
⊢ ∀x,y,z:ℝ^2.  (d(x;y) d(x;z) ⇐⇒ ||z x|| d(x;y))
BY
((UnivCD THENA Auto) THEN Fold `real-vec-dist` THEN (Assert d(x;z) d(z;x) BY Auto) THEN Auto) }


Latex:


Latex:
.....assertion..... 
1.  a  :  \mBbbR{}\^{}2
2.  b  :  \mBbbR{}\^{}2
3.  c  :  \mBbbR{}\^{}2
4.  d  :  \mBbbR{}\^{}2
5.  a  \mneq{}  c
6.  \mdownarrow{}\mexists{}p,q:\mBbbR{}\^{}2.  (((d(a;b)  =  d(a;p))  \mwedge{}  (d(c;d)  =  d(c;q)))  \mwedge{}  (d(c;p)  \mleq{}  d(c;d))  \mwedge{}  (d(a;q)  \mleq{}  d(a;b)))
7.  \mexists{}u,v:\mBbbR{}\^{}2
        (((||u||  =  d(a;b))  \mwedge{}  (||u  -  c  -  a||  =  d(c;d)))
        \mwedge{}  ((||v||  =  d(a;b))  \mwedge{}  (||v  -  c  -  a||  =  d(c;d)))
        \mwedge{}  (((d(a;b)\^{}2  -  d(c;d)\^{}2)  +  ||c  -  a||\^{}2\^{}2  <  (r(4)  *  ||c  -  a||\^{}2  *  d(a;b)\^{}2))
            {}\mRightarrow{}  (r2-left(u;c  -  a;\mlambda{}i.r0)  \mwedge{}  r2-left(v;\mlambda{}i.r0;c  -  a))))
\mvdash{}  \mforall{}x,y,z:\mBbbR{}\^{}2.    (d(x;y)  =  d(x;z)  \mLeftarrow{}{}\mRightarrow{}  ||z  -  x||  =  d(x;y))


By


Latex:
((UnivCD  THENA  Auto)  THEN  Fold  `real-vec-dist`  0  THEN  (Assert  d(x;z)  =  d(z;x)  BY  Auto)  THEN  Auto)




Home Index